Current approaches to the management of highly sensitized kidney transplant patients - Süsal, Caner; Morath, Christian (Tissue antigens, 2011)
With the introduction of sensitive antibody detection techniques, effective antibody elimination devices, therapeutic agents, such as bortezomib and eculizumab, and new concepts, such as Heidelberg algorithm, kidney paired exchange, and acceptable mismatch programs, several effective options are now available for the management of highly sensitized kidney transplant patients. However, as the number of human leukocyte antigen-mismatched transplantations is increasing with each year and as long as the elimination or long-term control of donor-specific antibody-producing clones remains an unresolved issue, sensitization will continue to represent a major problem in kidney transplantation.
Gesehen am 26.10.2022